Monotonic and cyclic responses of impact polypropylene and continuous glass fiber-reinforced impact polypropylene composites at different strain rates. (May 2016) - Yudhanto, A.; Lubineau, G.; Wafai, H.; Mulle, M.; Pulungan, D.; Yaldiz, R.; Verghese, N.
Abstract: Impact copolymer polypropylene (IPP), a blend of isotactic polypropylene and ethylene-propylene rubber, and its continuous glass fiber composite form (glass fiber-reinforced impact polypropylene, GFIPP) are promising materials for impact-prone automotive structures. However, basic mechanical properties and corresponding damage of IPP and GFIPP at different rates, which are of keen interest in the material development stage and numerical tool validation, have not been reported. Here, we applied monotonic and cyclic tensile loads to IPP and GFIPP at different strain rates (0.001/s, 0.01/s and 0.1/s) to study the mechanical properties, failure modes and the damage parameters. We used monotonic and cyclic tests to obtain mechanical properties and define damage parameters, respectively. We also used scanning electron microscopy (SEM) images to visualize the failure mode. We found that IPP generally exhibits brittle fracture (with relatively low failure strain of 2.69–3.74%) and viscoelastic-viscoplastic behavior. GFIPP [90]8 is generally insensitive to strain rate due to localized damage initiation mostly in the matrix phase leading to catastrophic transverse failure. In contrast, GFIPP [±45]s is sensitive to the strain rate as indicated by the change in shear modulus, shear strength and failure mode.